2014
DOI: 10.1038/clpt.2014.118
|View full text |Cite
|
Sign up to set email alerts
|

A Compartmental Pharmacokinetic Evaluation of Long-Acting Rilpivirine in HIV-Negative Volunteers for Pre-Exposure Prophylaxis

Abstract: Human immunodeficiency virus (HIV) pre-exposure prophylaxis (PrEP) refers to a strategy involving the use of antiretroviral (ARV) drugs to decrease the risk of HIV infection in uninfected individuals whose behavior would combine with local HIV prevalence to place them at high risk of infection. In 2012, the use of tenofovir disoproxil fumarate and emtricitabine (TDF/FTC) in combination was approved by the US Food and Drug Administration for use as PrEP, based on the results of the iPrEx 1-3 study and Partners … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
94
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(99 citation statements)
references
References 15 publications
(40 reference statements)
4
94
0
1
Order By: Relevance
“…Single-dose rilpivirine PK in plasma and in genital tracts of males (600 mg) and females (300, 600, and 1,200 mg) was assessed, and the drug was shown to persist for up to 84 days. The effect of rilpivirine concentrations in female genital tract fluid on HIV replication was also explored ex vivo (5). Studies to further evaluate long-acting rilpivirine as PrEP are planned (ClinicalTrials.gov identifier NCT02165202 [25]) or ongoing (ClinicalTrials.gov identifier NCT01656018 [26,27]).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Single-dose rilpivirine PK in plasma and in genital tracts of males (600 mg) and females (300, 600, and 1,200 mg) was assessed, and the drug was shown to persist for up to 84 days. The effect of rilpivirine concentrations in female genital tract fluid on HIV replication was also explored ex vivo (5). Studies to further evaluate long-acting rilpivirine as PrEP are planned (ClinicalTrials.gov identifier NCT02165202 [25]) or ongoing (ClinicalTrials.gov identifier NCT01656018 [26,27]).…”
Section: Discussionmentioning
confidence: 99%
“…Coformulated tenofovir DF-emtricitabine (Truvada; Gilead Sciences Ltd., London, United Kingdom) was approved by the U.S. Food and Drug Administration in 2012 for use as PrEP in high-risk individuals and in those engaging in sexual activity with HIV-infected partners (4). An intramuscularly administered, long-acting formulation of rilpivirine is also under investigation as a PrEP agent (5).…”
mentioning
confidence: 99%
“…Parenteral administration of the integrase strand-transfer inhibitor GSK1265744 (GSK744) fully protected rhesus macaques against repeated low-dose intrarectal challenges of SHIV162P3 (30). Monthly or bimonthly injections of longacting nanoparticulate formulations of GSK744 and the non- nucleoside reverse transcriptase inhibitor rilpivirine (RPV) are being investigated clinically as possible regimens for HIV therapy (25,27,31). HIV prophylaxis using long-acting NVP formulations.…”
Section: Discussionmentioning
confidence: 99%
“…This study is useful to decide the appropriate dose for HIV therapeutics. 8 In another study, the safety, tolerance, and pharmacokinetics of LA Rpv (TMC278, 300 mg/mL) formulation on administration, single and multiple intramuscular injection, in healthy volunteers were assessed by Verloes et al 9 The outcomes of this study suggested that a clinically relevant plasma concentration of Rpv could be optimized via tuning LA formulation. 9 Very recently, Margolis et al 10 presented a multicenter study based on long-acting ARV treatment enabling trial, for Phase IIb, using HIV-infected adults (.18 years old).…”
mentioning
confidence: 94%
“…Thus, monthly and bimonthly oral administration in the form of tablet would be enough to control HIV infection. 7 The multi-component pharmacokinetic evaluation of LA Rpv, 300 mg, 600 mg, or 1,200 mg (for 84 days), in 66 HIV-negative volunteers for preexposure prophylaxis was performed by Jackson et al 8 The authors assessed ex vivo antiviral activity of cervicovaginal lavage and claimed that each Rpv dose exhibited effective therapeutic effect, lasting till 84 days, upon exposure to plasma and genital tract. This study is useful to decide the appropriate dose for HIV therapeutics.…”
mentioning
confidence: 99%